Konsep Pendidikan Islam Dalam Perspektif Tafsir Al-Misbah Prof. Dr. H. Muhammad Quraish Shihab, MA. - Indah Nazaroh; Ismail; Abdul Rosip Siregar (Jurnal Penelitian dan Ilmu-Ilmu Keislaman, 2023)
Research results related to educational goals M. Quraish Shihab takes educational goals from the perspective of the Koran. M. Quraish Shihab stated that the purpose of education is to foster humans so that they realize that they are God's servants and carry out their functions as God's caliphs on this earth. Education according to M. Quraish Shihab must pay attention to three aspects in human beings, namely reason, soul and body. Mind development produces knowledge, soul development produces purity and ethics, and physical development produces skills. M. Quraish Shihab argues that educational goals lead to general educational goals or what are also called perfect goals. The perfect goal or ultimate goal of education according to M. Quraish Shihab must be able to form a two-dimensional human being who is balanced between reason and faith, reason and spiritual, and finally worldly and ukhrowi. Regarding learning methods in general, M. Quraish Shihab also takes an approach based on the Koran, which treats humans according to the elements of their creation, namely body, soul, and mind. Therefore M. Quraish Shihab did not propose a specific method of delivering the material. The most important thing in delivering material is sentences that inspire and touch the heart, accompanied by examples and habituation to solidify the material being taught. It can be concluded that the learning methods abstracted by M. Quraish Shihab from the Koran are very much in harmony with student-centered learning, this is because each method always pays attention to the condition of students, namely reason, physical and psychological.